In-situ experiment on critical thickness of brittle-ductile transition of single-crystal silicon - LIU Bing; XU Zong-wei; LI Rui; HE Zong-du (工程科学学报)
Single-crystal silicon is widely used in optoelectronics and micro-electromechanical systems because of its unique physical and chemical properties. Ductile-mode removal of single-crystal silicon can be realized by strictly controlling the cutting parameters, which significantly affect the machining efficiency. To improve the surface quality without reducing the machining efficiency, nanometric cutting experiments were performed using high-resolution scanning electron microscopy (SEM) with online observation. First, the samples were prepared, and the nanometric cutting edge of a diamond cutting tool was fabricated by focused ion beam (FIB) technology. Then, the initiation and propagation of the micro cracks were observed online by scanning electron microscopy to analyze the machining behavior of single-crystal silicon in brittle mode. Finally, using diamond cutting tools with edge radii of 40, 50, and 60 nm, respectively, the effects of crystal orientation and tool edge radius on the critical thickness of brittle-ductile transition of single-crystal silicon were studied. The experimental results show that in the presently studied crystal orientations, single-crystal silicon is most easily removed in the ductile mode along the[111] direction on the (111) plane, where the critical thickness of brittle-ductile transition is about 80 nm. In addition, the smaller the tool edge radius is, the more prone is the single-crystal silicon to brittle fracture in the nanocutting process. When the tool edge radius is 40 nm, the critical thickness of brittle-ductile transition is about 40 nm. However, the machined surface quality increases with decrease of the tool edge radius. This indicates that the sharper the cutting tool, the easier it is to obtain a high-quality surface.